Introduction: Quotas and Non-Quota Strategies in East Asia. Issue 1 (17th March 2015) - Tan, Netina
Abstract : In convergence with the global norm toward more proportional representative electoral systems, many countries in East Asia have adopted quota strategies to address women's political underrepresentation (Franceschet, Krook, and Piscopo 2012; Krook 2009). Taiwan, South Korea, Singapore, and Japan provide ideal case studies to investigate the impact of these efforts. While these countries share similar economic development, educational levels, and Confucian communitarian ethos, their experiences and progress on empowering women vary. For example, the level of women's legislative representation in the region ranges from a low of 8.1% in Japan to a high of 33.6% in Taiwan. And while Taiwan and South Korea embarked on constitutional reforms in the 1990s and introduced candidate quotas or reserved seats to guarantee women's legislative representation at all levels, Singapore and Japan have resisted legislating quotas but instead set 30% women parliamentarians as targets of party strategies. This collection of papers explores this intraregional variation with a comparative view on the origins and impact of quotas on women's political life. Specifically, we trace the origins of quota adoption and how they interact with the existing electoral and party institutions to improve women's legislative numbers.